Selection and characterization of siderophores of pathogenic Escherichia coli intestinal and extraintestinal isolates - Kumar Gulshan (De Gruyter, 2021)
Microorganisms adopt a unique mechanism for sequestration and transport of bound iron by producing iron-chelating molecules called siderophores. Siderophores play an important role in colonization of microbes in iron-deficient sites of the host, hence acting as an important virulence factor and promising carriers of antimicrobials to target sites inside the microbial cells. The research was conducted to identify and characterize the siderophores of pathogenic Escherichia coli isolates obtained from different parts of India. A total of 534 confirmed E. coli isolates were tested for the expression of siderophores using chrome azurol S agar method and its type were determined by Csaky and Arnow assays for hydroxamate and catecholate-type siderophores, respectively. The obtained results revealed a difference in siderophore-type expression by intestinal and extraintestinal pathogenic E. coli. On chrome azurol S agar 45.1% of pathogenic E. coli. were found to produce siderophores, 12.5% isolates were found to produce catechol-type siderophore and 35.4% isolates produced hydroxamate-type siderophore; and isolates could be classified into five sidero-types (1) only hydroxamate producing (2) only catechol producing (3) both catechol and hydroxamate producing (4) producing siderophores other than hydroxamate and catechol types and (5) siderophore non-producers. Siderophore production was detected in isolates from all geographical regions and in all seasons of the year. The findings conclude that siderophore production is one of the important virulence and epidemiological markers of intestinal as well as extraintestinal pathogenic E. coli.